Development of a Physics E-Module Integrated Local Wisdon and Problem Based Learning (PBL) to Increase Student Preparedness - Sahida, Desrianti; Huriati, Nining (Department of Physics Education, Universitas Mataram, 2024)
The goal of this research is to create e-module teaching materials based on PBL integrated with local wisdom in Physics subjects that are reliable, useful, and efficient. Research and development is the study's technique. The 4-D model, which consists of definition, design, development, and distribution, is the development model that is employed. An e-module with valid criteria (0.86) and practical criteria (94%) was achieved during the design stage, along with an early draft of the module that included the development stage and was effective for cognitive aspects (76%), effective in increasing preparedness (79%) was in the very ready category, the character category became a habit (86%), and moderate skills (87%). At the dissemination stage, it was found to be effective for the cognitive aspect (76.9%), effective in increasing preparedness (78.4%) in the very prepared category, character becomes a habit category (84%), and moderate skills (81.9%). It can be concluded that the developed e-module can improve students' preparedness by applying the PBL model integrated with local wisdom in accordance with the provisions of the Kurikulum Merdeka.